Це не нерівність, а рівняння
(3x-1)×(x-12)=0
3х²-х-36х+12=0
3х²-37х+12=0
Розв'яжемо рівняння через дискримінант.
D=b²-4ac
a=3 b= -37 c=12
D=(-37)²-4*3*12=1369-144=1225
x=
x₁==12
x₂==
Відповідь: 12; .
Це не нерівність, а рівняння
(3x-1)×(x-12)=0
3х²-х-36х+12=0
3х²-37х+12=0
Розв'яжемо рівняння через дискримінант.
D=b²-4ac
a=3 b= -37 c=12
D=(-37)²-4*3*12=1369-144=1225
x=![\frac{-b+-\sqrt{D}}{2a}](/tpl/images/1646/0649/2f4b9.png)
x₁=
=12
x₂=
=![\frac{1}{3}](/tpl/images/1646/0649/5506e.png)
Відповідь: 12;
.